2019
DOI: 10.1002/ajb2.1283
|View full text |Cite
|
Sign up to set email alerts
|

Pollen and vegetative secondary chemistry of three pollen‐rewarding lupines

Abstract: Premise Optimal defense theory predicts that selection should drive plants to disproportionally allocate resources for herbivore defense to tissues with high fitness values. Because pollen's primary role is the transport of gametes, plants may be expected to defend it from herbivory. However, for many animal‐pollinated plants, pollen serves a secondary role as a pollinator reward. These dual roles may present a conflict between selection to defend pollen from herbivores and selection to reward pollinators. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
(89 reference statements)
4
12
0
Order By: Relevance
“…When pollen is the primary reward, plants face the challenge of avoiding excessive pollen loss due to grooming while ensuring attractiveness to pollinators. In this issue, Heiling et al (2023) modeled pollen packaging strategies under the influence of these constraints, confirming the expectation that optimum package size depends on the relative preference of pollinators for larger packages, but also additional factors such as total pollen production in the population and possible relationships with per-plant visitation rates. The role of pollen as a reward in some species could be easily incorporated into fitness functions (Figure 1) by including links from pollen production (or daily presentation) to pollinator visitation.…”
Section: Pollen Production and Presentationsupporting
confidence: 58%
“…When pollen is the primary reward, plants face the challenge of avoiding excessive pollen loss due to grooming while ensuring attractiveness to pollinators. In this issue, Heiling et al (2023) modeled pollen packaging strategies under the influence of these constraints, confirming the expectation that optimum package size depends on the relative preference of pollinators for larger packages, but also additional factors such as total pollen production in the population and possible relationships with per-plant visitation rates. The role of pollen as a reward in some species could be easily incorporated into fitness functions (Figure 1) by including links from pollen production (or daily presentation) to pollinator visitation.…”
Section: Pollen Production and Presentationsupporting
confidence: 58%
“…In fact, they observed that some species in which pollen is completely inaccessible to bees had high concentrations of pyrrolizidine alkaloids. In addition, Fabaceae flowers have pollen hidden inside keel petals where it is accessible only to pollinators that effectively pollinate the flowers (Dunn, 1956), but nevertheless some Fabaceae species contain sufficient defence compounds in their pollen to impair pollinator development (Arnold et al, 2014;Heiling et al, 2019), or have been shown to be poor pollen sources for bee larvae (Haider et al, 2014). Second, in orchids, pollen is packaged in structures called pollinia, making it impossible for pollinators to exploit pollen from this plant family (Johnson & Edwards, 2000).…”
Section: Forummentioning
confidence: 99%
“…In support of this idea, Kessler & Halitschke () observed that concentrations of chlorogenic acid and rutin (a flavonoid) were correlated between leaves and pollen across individuals of Solanum peruvianum . However, Heiling et al () found that alkaloid content in pollen of Lupinus spp. was generally not correlated with the alkaloid content of flowers and vegetative tissues.…”
Section: Hypotheses To Explain the Existence Of Pollen Defence Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, smothering may be especially important if pollinators do not groom or cannot groom the areas of deposition. Another factor that may select for larger pollen loads is that pollen‐consuming pollinators may prefer plants or flowers with larger pollen loads (Heiling et al, 2023 [in this issue]). Importantly, our demonstration of pollen preclusion does not mean that smothering is not occurring simultaneously and having opposite effects on plant fitness.…”
Section: Discussionmentioning
confidence: 99%